High-Resolution Microfluidic Single-Cell Transcriptional Profiling Reveals Clinically Relevant Subtypes among Human Stem Cell Populations Commonly Utilized in Cell-Based Therapies - Rennert, Robert C.; Schäfer, Richard; Bliss, Tonya; Januszyk, Michael; Sorkin, Michael; Achrol, Achal S.; Rodrigues, Melanie; Maan, Zeshaan N.; Kluba, Torsten; Steinberg, Gary K.; Gurtner, Geoffrey C. (Frontiers in Neurology, 2016)
Stem cell therapies can promote neural repair and regeneration, yet controversy regarding optimal cell source and mechanism of action has slowed clinical translation, potentially due to undefined cellular heterogeneity. Single cell resolution is needed to identify clinically relevant subpopulations with the highest therapeutic relevance. We combine single cell microfluidic analysis with advanced computational modeling to study for the first time two common sources for cell-based therapies, human NSCs and MSCs. This methodology has the potential to logically inform cell source decisions for any clinical application.